The Effect of People Port Tulang Island as an Movement Economic Local Community - Rachman B, Arief; Budiman, Diky (Fakultas Perikanan dan Kelautan Universitas Riau, 2019)
This research was conducted from May to July 2018 in Tulang Island, Karimun Regency, Riau Islands Province.The purpose of this study is to understand the activities of community ports on Tulang Island and the economic driving factors of the Tulang Island community. The method used in this study is a qualitative method. Activities found from both people's port is the movement of people, goods and services. Economic driving factor in terms of trade slightly hampered in the process of loading and unloading goods, for service delivery factors there is no on the Tulang island, while fisheries and marine factors, in Tulang Island, it is in need of a decent port so that the process of loading catches such as shrimp, fish, and other commodities can be maximized.